The influence of the technical dimension, functional dimension, and tenant satisfaction on tenant loyalty: an analysis based on the theory of planned behavior - Lee, Chun-Chang; Ting, Lou-Jung; Yeh, Wen-Chih; Yu, Zheng (International Journal of Strategic Property Management, 2021)
This study primarily explored the influence of the technical dimension, functional dimension, and tenant satisfaction on tenant loyalty. The theory of planned behavior served as the basis of this study, and the three aforementioned factors (the technical dimension, the functional dimension, and tenant satisfaction) were incorporated into a conceptual framework for tenant loyalty. Structural equation modeling (SEM) was employed for parameter estimation. The participants consisted of tenants residing in eight administrative districts in Kaohsiung City. 315 questionnaires were administered, all of which were returned. After removing 15 invalid responses, there were 300 valid responses, which indicated an effective recovery rate of 95.2%. The results showed that the technical dimension, the functional dimension, and attitude significantly and positively influenced tenant satisfaction. Tenant satisfaction, perceived behavioral control, and social norms significantly and positively influenced tenant loyalty. Tenant satisfaction mediated the influence of the technical dimension and the functional dimension on tenant loyalty; the mediating effect of the functional dimension on tenant loyalty was greater than that of the technical dimension. The findings of this study highlight the measures rental companies should adopt in order to enhance the technical dimension, functional dimension, and tenant satisfaction, as this is crucial to maintaining sustainable operations.